The effects of a 6-week interdisciplinary rehabilitation program on physical function, pain, and fatigue in patients with long COVID. Observational study - Kristinn Birkisson 1993- (2024)
Abstract Background COVID-19 is a viral disease that caused a pandemic at the end of year 2019. The virus caused a disturbance to the everyday life of thousands of people as well as various health issues to those who contracted it. Common symptoms are fatigue, shortness of breath and physical pain. Symptoms that last longer than 12 weeks are considered chronic (i.e., long COVID). In Iceland, the prevalence of long COVID is estimated at around 7-8% of those who were infected. Long COVID patients experience persisting symptoms, affecting everyday function. Individuals with long-term symptoms need appropriate rehabilitation to gain better health, function, and quality of life. Objectives The aim of the study was to evaluate the effect of a 6-week interdisciplinary rehabilitation on individuals with long COVID symptoms, focusing on education and physical exercise as well as to assess whether they improved their physical function, experienced less pain and fatigue during daily activities, and if these benefits were maintained at a 6-month follow-up. Methods One hundred and eight participants (41 male and 67 female, average age 53.7 ± 12.7 years, average BMI 30.5 ± 5.9 kg/m2) underwent pre- and post-rehabilitation measurements. Outcomes used to assess physical function were: 6-Minute Walk Test (6-MWT), 1-Minute Sit-to-Stand Test (1-MSTST), 30 second Arm Curl Test and Grip Strength Test. Magnitude of pain and fatigue was measured on a self- assessment Numeric Rating Scale (NRS) from 0-10. Widespread Pain Index (WPI) was used to assess numbers of painful areas from 0-19. Participants were measured at admission and discharge, and 57 participants were measured at the 6-month follow-up. All participants took part in group education and a physical exercise training program, which was individually tailored, and had individualized therapies depending on their long COVID symptoms. Results Significant difference was found in all outcome measures for physical function, pain, and fatigue with p- score <0.001 between pre- and ...